2000
DOI: 10.1037/h0086854
|View full text |Cite
|
Sign up to set email alerts
|

Correlation, causation, motivation, and second language acquisition.

Abstract: It is well known to anyone who has taken even an introductory course in statistics that "correlation does not mean causation." This is a truism! The present article examines four truisms about correlation, demonstrating that they are not always true. For example, under certain conditions, correlation can imply causation, though these conditions are seldom satisfied in most applications. Nonetheless, there are many of us who are interested in investigating individual differences, and in making inferences of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
115
2
12

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(154 citation statements)
references
References 35 publications
6
115
2
12
Order By: Relevance
“…However, results revealed that the effect of motivation on English achievement is significantly greater when it is supported by the variables ALS and INT. Similar results have been reported by Bernaus and Gardner (2008) and Gardner (2000Gardner ( , 2001aGardner ( , 2001bGardner ( , 2005Gardner ( , 2007. Therefore, results of the SEM analysis confirmed the hypothesis that motivation has a positive effect on English achievement both directly and when it is affected by ALS and INT which themselves have mutual relationship.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…However, results revealed that the effect of motivation on English achievement is significantly greater when it is supported by the variables ALS and INT. Similar results have been reported by Bernaus and Gardner (2008) and Gardner (2000Gardner ( , 2001aGardner ( , 2001bGardner ( , 2005Gardner ( , 2007. Therefore, results of the SEM analysis confirmed the hypothesis that motivation has a positive effect on English achievement both directly and when it is affected by ALS and INT which themselves have mutual relationship.…”
Section: Resultssupporting
confidence: 87%
“…However, no significant direct causal relationship was found to exist between ALS and the learners' strategy use. This finding is contradictory to different studies which have shown that attitudes have played a significant role in the language learners' choice and application of learning strategies as well as successful second/foreign language learning (Gardner 2000, Kuramoto 2002, MacIntyre & Noels 1996. However the finding is in line with that of Gardner, Tremblay and Masgoret (1997).…”
Section: Resultscontrasting
confidence: 74%
See 2 more Smart Citations
“…This study was carried out in an study, they introduced Socio-educational Model of Second Language Acquisition in classroom settings which has later been revised many times (Gardner, 1985;Gardner & MacIntyre, 1993;Gardner & Trembley, 1995;Gardner, 2000). According to this approach, social psychology and individual psychology need to be integrated to describe the factor of motivation in the success of learning the target language.…”
Section: Literature Reviewmentioning
confidence: 99%